The 1996 and 1997 National Survey of Physician Asthma Management Practices: Background and Study Methodology - Robert L Jin; Bernard CK Choi (Canadian Respiratory Journal)
OBJECTIVES: To collect national baseline information on asthma management practices by physicians, and to compare these practices with the recommendations of the Canadian Asthma Consensus Conference (‘the guidelines’).